Two novel species of Urnula (Sarcosomataceae, Pezizales) from Yunnan, China - Lu, Jin-Rong; Yu, Feng-Ming; Zhou, De-Qun; Lu, Zhi-Yun; Zhang, Ying; Zhao, Qi (Phytotaxa, 2023)
Urnula is a prominent and older genus within the family Sarcosomataceae. Its members are widely distributed and have very similar features in the field. This study proposes two novel Urnula species collected from Yunnan Province, China. Detailed descriptions, illustrations, and phylogenetic analyses are provided. Urnula ailaoshanensis grows on rotten wood surrounded by moss and is characterized by its brighter hymenial surface, wider asci, and longer ascospores. Urnula subcrateria was collected on the soil humus layer of a subtropical forest with many fallen leaves, mosses, and lichens. It is morphologically and molecularly related to Urnula craterium (Schwein.) Fr., but can easily be distinguished by its shorter stipe and smaller asci and ascospores.